2016
DOI: 10.3892/mco.2016.1116
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of the prostate-specific antigen doubling time prior to and following radical prostatectomy to predict the outcome of prostate cancer

Abstract: Abstract. With the advent of serum prostate-specific antigen (PSA), a larger number of prostate cancers in the early phase have been successfully detected. Although decisions to perform prostate biopsies are routinely based on PSA levels, the PSA level is easily influenced by benign prostatic hyperplasia, with poor specificity. Therefore, the aim of the present study was to assess the clinical significance of prostatespecific antigen doubling time (PSADT) prior to and following radical prostatectomy. In total,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Commonly investigated indicators include the following. 1) Preoperative PSA: Most studies have concluded that a high level of preoperative PSA was associated with PSA recurrence,6,7,12–15 although Takeuchi16 and Aguilera17 reported insignificant results. Preoperative PSA doubling time (PSADT) has been a rising indicator in recent years, especially early PSADT and ultrasensitive PSADT, but their relationships with PSA recurrence are controversial 8.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Commonly investigated indicators include the following. 1) Preoperative PSA: Most studies have concluded that a high level of preoperative PSA was associated with PSA recurrence,6,7,12–15 although Takeuchi16 and Aguilera17 reported insignificant results. Preoperative PSA doubling time (PSADT) has been a rising indicator in recent years, especially early PSADT and ultrasensitive PSADT, but their relationships with PSA recurrence are controversial 8.…”
Section: Discussionmentioning
confidence: 99%
“…2) Pathological Gleason score: Much evidence has supported that a higher Gleason score increases the risk of PSA recurrence,7,1318 while a few studies have also reported insignificant results 12,19. 3) Pathological T stage: Generally, a higher T stage suggests a greater probability of developing PSA recurrence 7,12,1416. 4) Age: According to Wang et al, patients older than 70 years old were less likely to undergo PSA recurrence than those who were younger,12 although most other studies have reported an insignificant relationship between age and PSA recurrence 7,14,16,20,21.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PSA values at baseline and at 6 months of treatment were investigated for the mefenamic acid and placebo groups in the present study. According to the criteria of the Prostate Cancer Clinical Trials Working Group 3, this is a useful measurement to determine therapeutic efficacy and tumor progression in clinical trials (34,76).…”
Section: Time -------------------------------------------------------mentioning
confidence: 99%
“…(6) Pre-op PSA density, pre-op PSA velocity (PSAV) and pre and post-op PSA doubling time (PSADT) have also been shown to have prognostic value, however, none of these PSA metrics has reported a strong and consistent association with prostate cancerspecific mortality (PCSM). (7)(8)(9) Post-op PSAV and PSADT have not found widespread clinical favour as it is often necessary to wait for > 12 months for results which are problematic in view of the need to determine an (early) adjuvant therapy in recurrent disease. Previous studies have observed the lowest PSA level after RP (PSA nadir)…”
Section: Introductionmentioning
confidence: 99%